High-temperature lithium extraction adsorbent as well as preparation method and application thereof
By using spinel-type magnesium-aluminum oxide lithium-ion sieve as an adsorbent for high-temperature lithium extraction, combined with memory effect and coordination effect, the problems of low Li+ adsorption and insufficient stability of existing adsorbents at high temperatures are solved, and the stability of efficient lithium ion adsorption and multiple cycles are achieved.
Patent Information
- Application Number
- CN202411891738.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The existing lithium-extracting adsorbents show low Li+ adsorption amount and insufficient stability in high temperature and high pressure environments, making it difficult to meet the needs of geothermal fluid lithium extraction technology.
The spinel-type magnesium-aluminum oxide lithium-ion sieve is used as the adsorbent for high-temperature lithium extraction. Through memory effect and coordination effect, the efficient adsorption capacity of lithium ions is improved, and the pore volume and specific surface area of the adsorbent are increased through the introduction of pore-generating agents.
At 60~80°C, the Li+ saturation adsorption amount of the adsorbent is greater than 40 mg/g, and the adsorption amount of more than 35 mg/g is maintained after 30 cycles, which significantly improves the lithium ion selectivity and adsorption efficiency in the process of high-temperature lithium extraction.
Smart Images

Figure CN119549108A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an adsorbent for high-temperature lithium extraction and a preparation method and application thereof, belonging to the technical field of materials. Background Art
[0002] With the sharp increase in global demand for lithium, traditional lithium extraction methods can no longer meet market demand. Therefore, it is particularly important to explore new ways to extract lithium resources. Geothermal fluids are rich in lithium, and geothermal resources are widely distributed around the world, which provides huge potential for the development of geothermal fluid lithium extraction technology. The research on geothermal fluid lithium extraction technology not only helps to alleviate the contradiction between supply and demand of lithium resources, but also effectively utilizes geothermal resources and realizes the dual utilization of energy and mineral resources. This multiple utilization model not only enhances the economic value of geothermal resources, but also provides new ideas for the sustainable development of lithium resources. As an efficient lithium extraction material, adsorbents have gradually become a research hotspot due to their advantages such as good selectivity, large adsorption capacity and easy regeneration.
[0003] Patent 202211737926.X reports a Li 2 TiO 3 The preparation method of lithium extraction adsorbent achieves the characteristics of low titanium dissolution rate and good structural stability of the adsorbent by adding lithium source in steps, and high Li + Adsorption amount. Patent 202411338415.X reported a LiAl-LDHs@Al-MOFs core-shell lithium extraction adsorbent, which achieved highly selective adsorption and lithium extraction in salt lake brine with a high magnesium-lithium ratio at room temperature, and had good cyclic stability.
[0004] However, compared with the lithium extraction technology from salt lakes, the geothermal fluid lithium extraction technology requires the Li + The current lithium extraction adsorbents all have high-temperature Li + Due to the problems of low adsorption capacity and insufficient stability of adsorbents in lithium extraction environments under high temperature and high pressure, the research on geothermal fluid lithium extraction technology is still in its early stages. There are no reports on special adsorbents for geothermal fluid lithium extraction. It is of great significance to develop efficient adsorbents to extract lithium from geothermal fluids. Summary of the invention
[0005] The purpose of the present invention is to provide an adsorbent for high-temperature lithium extraction and a preparation method and application thereof in view of the above situation. The adsorbent is a spinel-type magnesium-aluminum oxide lithium ion sieve, which can achieve efficient adsorption of lithium ions in geothermal fluids. At about 60-80°C, the Li + The saturated adsorption capacity is greater than 40 mg / g, and after 30 cycles of use, the saturated adsorption capacity is greater than 35 mg / g, which can still achieve efficient adsorption of lithium ions.
[0006] At the same time, the present invention provides a method for preparing an adsorbent for high-temperature lithium extraction, through the memory effect, the adsorbent and Li + The coordination effect can achieve efficient adsorption of lithium ions and improve the lithium ion selectivity in the high-temperature lithium extraction process.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing an adsorbent for high-temperature lithium extraction comprises the following steps: Step 1, at room temperature, add aluminum source, magnesium source, lithium source, organic ligand, acid source and deionized water into a reaction kettle in sequence, and stir at 30-50° C. for 0.5-2 hours to obtain a precursor solution; the aluminum source and the magnesium source are fluoride-containing salts or chloride-containing salts; Step 2: at room temperature, prepare the porogen into a 0.05-0.15 mol / L (preferably 0.1 mol / L) N,N-dimethylformamide solution (i.e., the porogen is dissolved in the N,N-dimethylformamide solvent to form a porogen concentration of 0.05-0.15 mol / L N,N-dimethylformamide solution, and the solubility of the porogen in the system is increased by the solvent, and the porogen solution is dropwise added to the precursor solution prepared in step 1, and ultrasonically stirred for 1-2 h later, adding alkaline solution dropwise under ultrasonic stirring, adjusting the pH value of the solution to neutral, stirring in a constant temperature water bath at 60-90° C. for 2-5 h, crystallizing at 180-220° C. for 3-8 h (the crystallization reaction is used to form a uniform aluminum-magnesium-lithium skeleton structure, thereby forming a more stable lithium-magnesium-aluminum spinel), filtering, washing with solvent, drying at 140-160° C. for 10-24 h, and calcining at 1200-1500° C. for 10-24 h to obtain spinel-type lithium-magnesium-aluminum oxide; Step 3, at room temperature, add the spinel lithium magnesium aluminum oxide and the acidic solution prepared in step 2 into a reactor, oscillate at a constant temperature for 2 to 5 hours, filter, wash, dry at 80 to 120° C. for 10 to 24 hours, and calcine at 1200 to 1500° C. for 10 to 24 hours to obtain an adsorbent for high-temperature lithium extraction.
[0008] In step 1, the aluminum source is sodium hexafluoroaluminate or aluminum chloride; the magnesium source is magnesium fluoride or magnesium chloride; the lithium source is lithium hydroxide or lithium nitrate; the organic ligand is 2,2'-bipyridine or 2-methylimidazole; and the acid source is nitric acid or hydrochloric acid.
[0009] In step 1, the mass ratio of aluminum source, magnesium source, lithium source, organic ligand, acid source and deionized water is 1: (0.7-0.8): (0.1-0.3): (0.4-0.8): (0.1-0.3): (15-30). In the present invention, the specific magnesium-aluminum ratio is conducive to the adsorbent forming a more perfect spinel structure at high temperature.
[0010] In step 2, the porogen is polyethylene wax or polyvinyl alcohol; the alkaline solution is ammonia water or sodium carbonate solution, and the concentration of the sodium carbonate solution can be 0.01 mol / L.
[0011] In step 2, the mass ratio of the porogen solution to the precursor solution is (1-5): 1. If the proportion of the porogen is too small, an effective pore structure cannot be formed in the spinel lithium magnesium aluminum oxide, which affects the adsorption and diffusion of lithium ions during the lithium extraction process; if the concentration of the porogen is too high, the spinel lithium magnesium aluminum oxide structure is easily collapsed during the preparation process of the spinel lithium magnesium aluminum oxide.
[0012] In step 3, the acidic solution is 0.1-0.5 mol / L hydrochloric acid or nitric acid.
[0013] In step 3, the mass ratio of the acidic solution to the spinel lithium magnesium aluminum oxide is (600-800): 1, In steps 1 and 2, the stirring speed is 100-500 rpm.
[0014] In step 2, the ultrasonic stirring power is 1000~1500W and the temperature is 40~60℃.
[0015] In step 3, the temperature of the constant temperature oscillation is 30-50°C; The high temperature lithium extraction adsorbent obtained by the preparation method of the present invention has a Li + The saturated adsorption capacity is greater than 40 mg / g, and after 30 cycles of use, the saturated adsorption capacity is greater than 35 mg / g.
[0016] The present invention also discloses the use of the aforementioned high-temperature lithium extraction adsorbent as an adsorbent for geothermal fluid lithium extraction, as well as a preparation method of the aforementioned high-temperature lithium extraction adsorbent or the use of the high-temperature lithium extraction adsorbent in geothermal fluid lithium extraction.
[0017] The present invention has the following beneficial effects: (1) The high-temperature lithium extraction adsorbent prepared by the present invention adopts magnesium-aluminum spinel as the skeleton structure. Compared with other types of adsorbents, magnesium-aluminum spinel has a stable structure and good acid and alkali resistance, which ensures the structural stability of the lithium extraction adsorbent during high-temperature lithium extraction and recycling.
[0018] (2) In the process of preparing the adsorbent for high-temperature lithium extraction, the present invention introduces nitrogen-containing organic ligands, and the nitrogen atoms in the organic ligands form coordination bonds with metal ions, so that aluminum, magnesium, and lithium are evenly dispersed in the spinel-type lithium magnesium aluminum oxide, thereby increasing the density of lithium ion holes in the high-temperature lithium extraction adsorbent and the structural uniformity of the magnesium aluminum spinel type in the high-temperature lithium extraction adsorbent, and further enhancing the structural stability of the adsorbent during the high-temperature lithium extraction process. At the same time, the nitrogen atoms in the nitrogen-containing organic ligands can cooperate with fluorine and chlorine ions, and fluorine or chlorine can easily form ionic bonds with strong polarity with lithium ions, resulting in lithium ions being difficult to desorb. The competitive adsorption of nitrogen atoms and fluorine or chlorine on lithium ions effectively weakens the polarity of the ionic bonds that fluorine or chlorine can easily form with lithium ions, thereby facilitating the desorption of lithium ions after the adsorbent is used for high-temperature lithium extraction, thereby ensuring that the adsorbent for high-temperature lithium extraction still maintains a high adsorption capacity after multiple cycles.
[0019] (3) During high-temperature lithium extraction, the diffusion rate of lithium ions is fast due to the high temperature. Therefore, compared with normal-temperature lithium extraction, there are problems of low lithium extraction rate and low adsorption amount. In the process of preparing the adsorbent for high-temperature lithium extraction of the present invention, the pore volume and specific surface area inside the adsorbent are effectively increased by introducing a porogen. The larger pore volume is conducive to the formation of a local lithium ion pool with a stable concentration inside the adsorbent during the high-temperature lithium extraction process, further improving the adsorption rate of the adsorbent during the high-temperature lithium extraction process; the large specific surface area can effectively increase the mass transfer rate of lithium ions on the surface of the adsorbent and the accessibility of lithium ion holes during the high-temperature lithium extraction process, thereby increasing the adsorption rate and adsorption amount of lithium ions of the adsorbent.
[0020] Because the nitrogen atoms in the organic ligands form coordination bonds with the metal ions, and the lone pair electrons of the introduced fluorine or chlorine atoms form a stable coordination structure with the lithium ions, combined with the screening and memory effects of lithium ion holes, lithium ions can effectively stay after entering the pores in the adsorbent at high temperatures, thereby forming a lithium ion pool with a stable concentration in the pores with a larger pore volume. Lithium ions can also effectively stay on the specific surface of the adsorbent and be better adsorbed.
[0021] (4) During high-temperature lithium extraction, due to the high temperature, conventional adsorbents have weak binding force with lithium ions, and the lithium ions adsorbed by the adsorbents are easily desorbed, resulting in a low amount of lithium adsorption. Fluorine or chlorine elements are introduced into the adsorbent for high-temperature lithium extraction prepared by the present invention. During high-temperature lithium extraction, on the basis of achieving adsorption and extraction of lithium ions through the screening and memory effect of lithium ion holes, the lone pair electrons of the introduced fluorine or chlorine atoms can form a stable coordination structure with lithium ions, which can effectively improve the binding force of the adsorbent on lithium ions during high-temperature lithium extraction, effectively prevent the desorption and detachment of the adsorbed lithium ions from the adsorbent, thereby increasing the amount of lithium ions adsorbed during high-temperature lithium extraction. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1This is the XRD diagram of the adsorbent for high-temperature lithium extraction in Example 1. DETAILED DESCRIPTION
[0023] The present invention will be further described in detail below in conjunction with specific examples. The following examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0024] Example 1
[0025] At room temperature, 10 g of sodium hexafluoroaluminate, 7.5 g of magnesium fluoride, 2 g of lithium nitrate, 6 g of 2,2'-bipyridine, 2 g of nitric acid, and 200 g of water were added to a reaction kettle in sequence, and stirred at 40° C. and 300 rpm for 1 h to obtain a precursor solution; At room temperature, polyvinyl alcohol was prepared into a 0.1 mol / L N,N-dimethylformamide solution (porogen solution), 600 g of the porogen solution was added dropwise to the precursor solution, and ultrasonic stirring was performed at 1200 W and 50° C. for 1.5 h. Ammonia water was added dropwise under ultrasonic stirring to adjust the pH of the solution to neutral. The solution was stirred at 300 rpm in a constant temperature water bath at 80° C. for 3 h, and then crystallized at 200° C. for 5 h, filtered, washed with N,N-dimethylformamide solvent, dried at 150° C. for 12 h, and calcined at 1400° C. for 12 h to obtain spinel lithium magnesium aluminum oxide. At room temperature, 10g of spinel lithium magnesium aluminum oxide and 6000g of 0.3 mol / L nitric acid solution were added to the reactor, and the mixture was oscillated at 40°C for 3h, filtered, washed, dried at 100°C for 12h, and calcined at 1400°C for 12h to obtain an adsorbent for high-temperature lithium extraction. The specific surface area of the prepared adsorbent for high-temperature lithium extraction is 356m 2 / g.
[0026] Test process: Prepare 0.05mol / L LiCl solution, adjust the pH to about 12 with LiOH solution, take 100mL of the above solution into a stoppered shake bottle, add 0.1g of high temperature lithium extraction adsorbent at 80℃, shake on a shaker, and conduct Li + Adsorption experiment, determine the saturated adsorption amount and saturated adsorption time of the adsorbent for high-temperature lithium extraction. At 25°C, add 0.5g of saturated adsorbent for high-temperature lithium extraction into 250mL of 0.5mol / L hydrochloric acid solution, and regenerate by acid leaching for 2h under stirring. After regeneration, perform cyclic adsorption experiment to test the cyclic adsorption performance of the adsorbent for high-temperature lithium extraction.
[0027] Figure 1 The XRD diagram of the adsorbent for high temperature lithium extraction in Example 1 shows that the adsorbent for high temperature lithium extraction prepared by the present invention has a typical magnesium aluminum spinel structure and has a high degree of crystallinity. The adsorbent prepared in this example has a Li +The saturated adsorption time is 12h, the saturated adsorption capacity is 49mg / g, and the saturated adsorption capacity is 38mg / g after 30 cycles.
[0028] Example 2
[0029] At room temperature, 10 g aluminum chloride, 7 g magnesium chloride, 1 g lithium hydroxide, 4 g 2-methylimidazole, 1 g hydrochloric acid, and 150 g water were added to the reaction kettle in sequence, and stirred at 30° C. and 500 rpm for 1 h to obtain a precursor solution; At room temperature, polyethylene wax was prepared into a 0.1 mol / L N,N-dimethylformamide solution (porogen solution), 300 g of the porogen solution was added dropwise to the precursor solution, and ultrasonic stirring was performed at 1500 W and 60° C. for 1 hour. Ammonia water was added dropwise under ultrasonic stirring to adjust the pH of the solution to neutral. The solution was stirred at 60° C. and 500 rpm for 3 hours in a constant temperature water bath, and then crystallized at 220° C. for 3 hours, filtered, washed with N,N-dimethylformamide solvent, dried at 150° C. for 12 hours, and calcined at 1500° C. for 10 hours to obtain spinel lithium magnesium aluminum oxide. At room temperature, 10g of spinel lithium magnesium aluminum oxide and 8000g of 0.1 mol / L hydrochloric acid solution were added to the reactor, and the mixture was oscillated at 50°C for 2h, filtered, washed, dried at 100°C for 12h, and calcined at 1500°C for 10h to obtain an adsorbent for high-temperature lithium extraction. The specific surface area of the prepared adsorbent for high-temperature lithium extraction is 338m 2 / g.
[0030] The test was performed using the test process in Example 1.
[0031] The adsorbent prepared in this example was Li + The saturated adsorption time is 15h, the saturated adsorption capacity is 47mg / g, and the saturated adsorption capacity is 39mg / g after 30 cycles.
[0032] Example 3
[0033] At room temperature, 10 g of sodium hexafluoroaluminate, 8 g of magnesium fluoride, 3 g of lithium nitrate, 8 g of 2-methylimidazole, 3 g of nitric acid, and 180 g of water were added to a reaction kettle in sequence, and stirred at 50° C. and 100 rpm for 2 h to obtain a precursor solution; At room temperature, polyvinyl alcohol was prepared into a 0.1 mol / L N,N-dimethylformamide solution (porogen solution), 250 g of the porogen solution was added dropwise to the precursor solution, and ultrasonic stirring was performed at 1000 W and 60° C. for 1 h. Ammonia water was added dropwise under ultrasonic stirring to adjust the pH of the solution to neutral. The solution was stirred at 90° C. and 100 rpm for 3 h in a constant temperature water bath, and then crystallized at 180° C. for 3 h, filtered, washed with N,N-dimethylformamide solvent, dried at 150° C. for 12 h, and calcined at 1200° C. for 16 h to obtain spinel lithium magnesium aluminum oxide. At room temperature, 10g of spinel lithium magnesium aluminum oxide and 7000g of 0.1 mol / L nitric acid solution were added to the reactor, and the mixture was shaken at 30°C for 5h, filtered, washed, dried at 100°C for 12h, and calcined at 1200°C for 16h to obtain an adsorbent for high-temperature lithium extraction. The specific surface area of the prepared adsorbent for high-temperature lithium extraction is 328m 2 / g.
[0034] The test was performed using the test process in Example 1.
[0035] The adsorbent prepared in this example was Li + The saturated adsorption time is 13h, the saturated adsorption capacity is 46mg / g, and the saturated adsorption capacity is 36mg / g after 30 cycles.
[0036] Comparative Example 1 Omitting the addition of porogen At room temperature, 10 g of sodium hexafluoroaluminate, 7.5 g of magnesium fluoride, 2 g of lithium nitrate, 6 g of 2,2'-bipyridine, 2 g of nitric acid, and 200 g of water were added to a reaction kettle in sequence, and stirred at 40° C. and 300 rpm for 1 h to obtain a precursor solution; At room temperature, ammonia water was added dropwise to the precursor solution under ultrasonic stirring, the pH value of the solution was adjusted to neutral, and the solution was stirred at 300 rpm in a constant temperature water bath at 80°C for 3 hours, then crystallized at 200°C for 5 hours, filtered, washed with N,N-dimethylformamide solvent, dried at 150°C for 12 hours, and calcined at 1400°C for 12 hours to obtain spinel lithium magnesium aluminum oxide; At room temperature, 10g of spinel lithium magnesium aluminum oxide and 6000g of 0.3 mol / L nitric acid solution were added to the reactor, and the mixture was shaken at 40°C for 3h, filtered, washed, dried at 100°C for 12h, and calcined at 1400°C for 12h to obtain an adsorbent for high-temperature lithium extraction. The specific surface area of the prepared adsorbent for high-temperature lithium extraction is 197m 2 / g.
[0037] The test was performed using the test process in Example 1.
[0038] The adsorbent prepared in this comparative example has a Li +The saturated adsorption time is 18h, the saturated adsorption capacity is 32mg / g, and the saturated adsorption capacity is 20mg / g after 30 cycles.
[0039] As can be seen from Comparative Example 1, compared with the embodiment, since no porogen is added to the preparation system of the adsorbent for high temperature lithium extraction in the comparative example, the specific surface area of the prepared adsorbent for high temperature lithium extraction is smaller (<200m 2 / g), therefore, the amount of lithium adsorbed is low during high-temperature lithium extraction.
[0040] Comparative Example 2 Omitting the introduction of fluorine / chlorine elements At room temperature, 10 g aluminum nitrate, 7.5 g magnesium nitrate, 2 g lithium nitrate, 6 g 2,2'-bipyridine, 2 g nitric acid, and 200 g water were added to the reaction kettle in sequence, and stirred at 40° C. and 300 rpm for 1 h to obtain a precursor solution; At room temperature, polyvinyl alcohol was prepared into a 0.1 mol / L N,N-dimethylformamide solution (porogen solution), 600 g of the porogen solution was added dropwise to the precursor solution, and ultrasonic stirring was performed at 1200 W and 50° C. for 1.5 h. Ammonia water was added dropwise under ultrasonic stirring to adjust the pH of the solution to neutral. The solution was stirred at 300 rpm in a constant temperature water bath at 80° C. for 3 h, and then crystallized at 200° C. for 5 h, filtered, washed with N,N-dimethylformamide solvent, dried at 150° C. for 12 h, and calcined at 1400° C. for 12 h to obtain spinel lithium magnesium aluminum oxide. At room temperature, 10g of spinel lithium magnesium aluminum oxide and 6000g of 0.3 mol / L nitric acid solution were added to the reactor, and the mixture was oscillated at 40°C for 3h, filtered, washed, dried at 100°C for 12h, and calcined at 1400°C for 12h to obtain an adsorbent for high-temperature lithium extraction. The specific surface area of the prepared adsorbent for high-temperature lithium extraction is 296m 2 / g.
[0041] The test was performed using the test process in Example 1.
[0042] The adsorbent prepared in this comparative example has a Li + The saturated adsorption time is 24h, the saturated adsorption capacity is 26mg / g, and the saturated adsorption capacity is 13mg / g after 30 cycles.
[0043] It can be seen from Comparative Example 2 that, compared with the embodiment, in the comparative example, since no fluorine or chlorine elements are introduced into the adsorbent preparation system for high-temperature lithium extraction, it is difficult to reach a balance between the adsorption and desorption of lithium ions on the adsorbent during the high-temperature lithium extraction process, resulting in a prolonged saturated adsorption time of lithium ions, and in a high-temperature environment, the adsorption and binding force of lithium ions is limited only by the screening and memory effect of lithium ion vacancies, and lithium ions are easily desorbed from the adsorbent, resulting in a decrease in the adsorption amount of lithium ions during the high-temperature lithium extraction process.
[0044] Comparative Example 3: Replacement of nitrogen-free organic ligand At room temperature, 10 g of sodium hexafluoroaluminate, 7.5 g of magnesium fluoride, 2 g of lithium nitrate, 6 g of methyl trimesic acid, 2 g of nitric acid, and 200 g of water were added to a reaction kettle in sequence, and stirred at 40° C. and 300 rpm for 1 hour to obtain a precursor solution; At room temperature, polyvinyl alcohol was prepared into a 0.1 mol / L N,N-dimethylformamide solution (porogen solution), 600 g of the porogen solution was added dropwise to the precursor solution, and ultrasonic stirring was performed at 1200 W and 50° C. for 1.5 h. Ammonia water was added dropwise under ultrasonic stirring to adjust the pH of the solution to neutral. The solution was stirred at 300 rpm in a constant temperature water bath at 80° C. for 3 h, and then crystallized at 200° C. for 5 h, filtered, washed with N,N-dimethylformamide solvent, dried at 150° C. for 12 h, and calcined at 1400° C. for 12 h to obtain spinel lithium magnesium aluminum oxide. At room temperature, 10g of spinel lithium magnesium aluminum oxide and 6000g of 0.3 mol / L nitric acid solution were added to the reactor, and the mixture was oscillated at 40°C for 3h, filtered, washed, dried at 100°C for 12h, and calcined at 1400°C for 12h to obtain an adsorbent for high-temperature lithium extraction. The specific surface area of the prepared adsorbent for high-temperature lithium extraction is 274m 2 / g.
[0045] The test was performed using the test process in Example 1.
[0046] The adsorbent prepared in this comparative example has a Li + The saturated adsorption time is 15h, the saturated adsorption capacity is 46mg / g, and the saturated adsorption capacity is 23mg / g after 30 cycles.
[0047] It can be seen from Comparative Example 3 that, compared with the embodiment, in the comparative example, since no nitrogen-containing organic ligand is used in the preparation system of the adsorbent for high-temperature lithium extraction, but methyl trimesic acid is used as the organic ligand, the adsorbent for high-temperature lithium extraction shows a higher saturated adsorption capacity in the first adsorption, but after multiple cycles of use, the saturated adsorption capacity decreases rapidly.
[0048] The above embodiments are only used to illustrate the technical solutions of the present invention. Those skilled in the art should understand that the above embodiments do not limit the present invention in any form, and any technical solutions obtained by equivalent replacement or equivalent transformation shall fall within the protection scope of the present invention.
Claims
1. A method for preparing an adsorbent for high-temperature lithium extraction, characterized in that: The following steps are involved: Step 1, at room temperature, add aluminum source, magnesium source, lithium source, organic ligand, acid source and deionized water into a reaction kettle in sequence, and stir at 30-50° C. for 0.5-2 hours to obtain a precursor solution; the aluminum source and the magnesium source are fluoride-containing salts or chloride-containing salts; Step 2, at room temperature, prepare a porogen into a 0.05-0.15 mol / L N,N-dimethylformamide solution, add the precursor solution prepared in step 1 dropwise, and ultrasonically stir for 1-2 hours, then dropwise add an alkali solution under ultrasonic stirring, adjust the pH of the solution to neutral, and stir in a constant temperature water bath at 60-90° C. for 2-5 hours, and then crystallize at 180-220° C. for 3-8 hours, filter, wash with a solvent, dry at 140-160° C. for 10-24 hours, and calcine at 1200-1500° C. for 10-24 hours to obtain spinel lithium magnesium aluminum oxide; Step 3, at room temperature, add the spinel lithium magnesium aluminum oxide and the acidic solution prepared in step 2 into a reactor, oscillate at a constant temperature for 2 to 5 hours, filter, wash, dry at 80 to 120° C. for 10 to 24 hours, and calcine at 1200 to 1500° C. for 10 to 24 hours to obtain an adsorbent for high-temperature lithium extraction.
2. The preparation method according to claim 1, characterized in that: In step 1, the aluminum source is sodium hexafluoroaluminate or aluminum chloride; and the magnesium source is magnesium fluoride or magnesium chloride.
3. The preparation method according to claim 1, characterized in that: In step 1, the lithium source is lithium hydroxide or lithium nitrate; the organic ligand is 2,2'-bipyridine or 2-methylimidazole; the acid source is nitric acid or hydrochloric acid; the mass ratio of the aluminum source, magnesium source, lithium source, organic ligand, acid source and deionized water is 1: (0.7~0.8): (0.1~0.3): (0.4~0.8): (0.1~0.3): (15~30).
4. The preparation method according to claim 1, characterized in that: In step 2, the porogen is polyethylene wax or polyvinyl alcohol; the alkaline solution is ammonia water or 0.01 mol / L sodium carbonate solution; and the mass ratio of the porogen solution to the precursor solution is (1-5):
1.
5. The preparation method according to claim 1, characterized in that: In step 3, the acidic solution is 0.1-0.5 mol / L hydrochloric acid or nitric acid; the mass ratio of the acidic solution: spinel lithium magnesium aluminum oxide is (600-800):
1.
6. The preparation method according to claim 1, characterized in that: In steps 1 and 2, the stirring rate is 100-500 rpm; in step 2, the ultrasonic stirring power is 1000-1500 W, and the temperature is 40-60° C. In step 3, the temperature of the constant temperature oscillation is 30-50° C.
7. An adsorbent for high-temperature lithium extraction obtained by the preparation method according to any one of claims 1 to 6.
8. The adsorbent for high temperature lithium extraction according to claim 7, characterized in that: The adsorbent Li + The saturated adsorption capacity is greater than 40 mg / g, and after 30 cycles of use, the saturated adsorption capacity is greater than 35 mg / g.
9. Use of the adsorbent for high-temperature lithium extraction according to claim 7 as an adsorbent for lithium extraction from geothermal fluids.
10. A method for preparing the adsorbent for high-temperature lithium extraction according to any one of claims 1 to 6 or use of the adsorbent for high-temperature lithium extraction according to claim 7 in extracting lithium from geothermal fluids.
Citation Information
Patent Citations
CeO2 modified nanometer Ag whisker doped graphene film and preparation method thereof
CN111822308A
Method for selectively extracting lithium from lithium-containing wastewater by using fluorine-containing polymer adsorbent
CN114134342A
Porous lithium adsorbent and preparation method and application thereof
CN114917862A
Adsorbent for extracting lithium from whisker-shaped spinel type magnesium-aluminum oxide lithium ion sieve salt lake and preparation method of adsorbent for extracting lithium from whisker-shaped spinel type magnesium-aluminum oxide lithium ion sieve salt lake
CN116078344A
Preparation method for modifying fluorine-containing functional group adsorbent by taking cellulose as carrier
CN116173915A